Deep learning for screening primary osteopenia and osteoporosis using spine radiographs and patient clinical covariates in a Chinese population - Mao, Liting; Xia, Ziqiang; Pan, Liang; Chen, Jun; Liu, Xian; Li, Zhiqiang; Yan, Zhaoxian; Lin, Gengbin; Wen, Huisen; Liu, Bo (Frontiers in Endocrinology, 2022)
Purpose: Many high-risk osteopenia and osteoporosis patients remain undiagnosed. We proposed to construct a convolutional neural network model for screening primary osteopenia and osteoporosis based on the lumbar radiographs, and to compare the diagnostic performance of CNN model adding the clinical covariates with the image model alone. Methods: 6908 participants were collected for analysis, including postmenopausal women and men aged 50-95 years, who performed conventional lumbar X-ray examinations and dual-energy X-ray absorptiometry(DXA) examinations within 3 months. All participants were divided into the training set, validation set, test set1, and test set2 at a ratio of 8:1:1:1. The bone mineral density(BMD) values derived from DXA were applied as the reference standard. A 3-class CNN model was developed to classify the patients into normal BMD, osteopenia, and osteoporosis. Moreover, we developed the models integrating the images with clinical covariates (age, gender, BMI), and explored whether adding clinical data improves diagnostic performance over the image mode alone. The receiver operating characteristic curve analysis was performed for assessing the model performance. Results: As for classifying osteoporosis, the model based on the anteroposterior+lateral channel performed best, with the area under the curve(AUC) range from 0.909 to 0.937 in three testing cohorts. The models with images alone achieved moderate sensitivity in classifying osteopenia, in which the highest AUC achieved 0.785. The performance of models integrating images with clinical data shown a slight improvement over models with anteroposterior or lateral images input alone for diagnosing osteoporosis, in which the AUC increased about 2–4%. Regarding categorizing osteopenia and the normal BMD, the proposed models integrating images with clinical data also outperformed the models with images solely. Conclusion: The deep learning-based approach could screen osteoporosis and osteopenia based on lumbar radiographs.